Determination of Hg(II) and Methylmercury by Electrothermal Atomic Absorption Spectrometry after Dispersive Solid-Phase Microextraction with a Graphene Oxide Magnetic Material - Yesica Vicente-Martínez; María Jose Muñoz-Sandoval; Manuel Hernandez-Cordoba; Ignacio Lopez-Garcia (Molecules, 2022)
The toxicity of all species of mercury makes it necessary to implement analytical procedures capable of quantifying the different forms this element presents in the environment, even at very low concentrations. In addition, due to the assorted environmental and health consequences caused by each mercury species, it is desirable that the procedures are able to distinguish these forms. In nature, mercury is mainly found as Hg0, Hg2+ and methylmercury (MeHg), with the latter being rapidly assimilated by living organisms in the aquatic environment and biomagnified through the food chain. In this work, a dispersive solid-phase microextraction of Hg2+ and MeHg is proposed using as the adsorbent a magnetic hybrid material formed by graphene oxide and ferrite (Fe3O4@GO), along with a subsequent determination by electrothermal atomic absorption spectrometry (ETAAS). On the one hand, when dithizone at a pH = 5 is used as an auxiliary agent, both Hg(II) and MeHg are retained on the adsorbent. Next, for the determination of both species, the solid collected by the means of a magnet is suspended in a mixture of 50 µL of HNO3 (8% v/v) and 50 µL of H2O2 at 30% v/v by heating for 10 min in an ultrasound thermostatic bath at 80 °C. On the other hand, when the sample is set at a pH = 9, Hg(II) and MeHg are also retained, but if the solid collected is washed with N-acetyl-L-cysteine only, then the Hg(II) remains on the adsorbent, and can be determined as indicated above. The proposed procedure exhibits an enrichment factor of 49 and the determination presents a linear range between 0.1 and 10 µg L−1 of mercury. The procedure has been applied to the determination of mercury in water samples from different sources.